An overview of patient involvement in healthcare decision-making: a situational analysis of the Malaysian context - Ng, Chirk Jenn; Lee, Ping Yein; Lee, Yew Kong; Chew, Boon How; Engkasan, Julia Patrick; Ismail, Irmi Zarina; Hanafi, Nik Sherina Haidi; Tong, Seng Fah (BioMed Central, 2013)
Background: Involving patients in decision-making is an important part of patient-centred care. Research has found a discrepancy between patients’ desire to be involved and their actual involvement in healthcare decision-making. In Asia, there is a dearth of research in decision-making. Using Malaysia as an exemplar, this study aims to review the current research evidence, practices, policies, and laws with respect to patient engagement in shared decision-making (SDM) in Asia. Methods: In this study, we conducted a comprehensive literature review to collect information on healthcare decision-making in Malaysia. We also consulted medical education researchers, key opinion leaders, governmental organisations, and patient support groups to assess the extent to which patient involvement was incorporated into the medical curriculum, healthcare policies, and legislation. Results: There are very few studies on patient involvement in decision-making in Malaysia. Existing studies showed that doctors were aware of informed consent, but few practised SDM. There was limited teaching of SDM in undergraduate and postgraduate curricula and a lack of accurate and accessible health information for patients. In addition, peer support groups and 'expert patient’ programmes were also lacking. Professional medical bodies endorsed patient involvement in decision-making, but there was no definitive implementation plan. Conclusion: In summary, there appears to be little training or research on SDM in Malaysia. More research needs to be done in this area, including baseline information on the preferred and actual decision-making roles. The authors have provided a set of recommendations on how SDM can be effectively implemented in Malaysia.